Recurrent Otorrhea in A Child: Early Sign of Temporal Bone Langerhans Cell Histiocytosis - Mohd Zulkefli, N; BS, Goh; Amri, F; Tan, GC (IIUM Medical Journal Malaysia, 2020)
Langerhans cell histiocytosis (LCH) is a rare disease of dendritic origin with uncertain etiology, with predilection in children. A 1-year 6-month girl with history of recurrent otorrhea, presented with mass in the ear canal and computed tomography imaging showed expansile lytic bony lesion in right mastoid with eroded ossicles. Subsequently, histopathological examination confirmed the diagnosis of LCH and chemotherapy was successfully commenced with complete resolution of symptoms. LCH with ear involvement are usually mistaken as other acute or chronic ear disease such as chronic otitis media or mastoiditis. Hence, in children with recurrent otorrhea with ear canal mass, with or without facial nerve palsy, LCH should be considered as one of the differential diagnosis.